Computer Safety, Reliability, and Security 30th International Conference, SAFECOMP 2011, Naples, Italy, September 19-22, 2011, Proceedings - Flammini, Francesco; Bologna, Sandro; Vittorini, Valeria; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
This book constitutes the refereed proceedings of the 30th International Conference on Computer Safety, Reliability, and Security, SAFECOMP 2011, held in Naples, Italy, in September 2011. The 34 full papers presented together were carefully reviewed and selected from 100 submissions. The papers are organized in topical sections on RAM evaluation, complex systems dependability, formal verification, risk and hazard analysis, cybersecurity and optimization methods.
Keywords: Computer security; Computer communication systems; Software engineering; Algorithms; Computers and civilization; Special purpose computers; Systems and Data Security; Computer Communication Networks; Software Engineering; Algorithm Analysis and Problem Complexity; Computers and Society; Special Purpose and Application-Based Systems